Leading Difficult Conversations Series #3: Creating a Safe Conversation Environment - Christy Chiarelli (EDIS)
This publication series is intended for leaders who bear the responsibility of having difficult conversations as part of their professional responsibilities. Earlier in this publication series, the foundational principles of preparing for difficult conversations were established: (1) defining the issue and (2) determining your motive for the conversation. Once those principles are put into practice, the next phase of having a difficult conversation is creating a safe environment for the conversation. Components of creating a safe environment include recognizing a conversation’s content and conditions, understanding the threats to a safe environment, and utilizing skills to overcome threats to restore safety. This new 3-page publication of the UF/IFAS Department of Agricultural Education and Communication was written by Christy Chiarelli. https://edis.ifas.ufl.edu/wc384